2021
DOI: 10.3389/fonc.2020.607231
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of circRNA circ_0087378 Represses the Tumorigenesis and Progression of Esophageal Squamous Cell Carcinoma Through Modulating the miR-140-3p/E2F3 Axis

Abstract: BackgroundWe aimed to investigate the function and underlying mechanisms of circ_0087378 in esophageal squamous cell carcinoma (ESCC).MethodsWe verified higher circ_0087378 expression in ESCC tissues by performing qRT-PCR assays. We further confirmed the oncogenic roles of circ_0087378 in ESCC cells through a series of biological function assays. Then, we used an RNA pull-down assay and luciferase reporter assay to identify miR-140-3p that directly interacts with circ_0087378. Subsequent studies were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…29 Likewise, E2F3 had elevated levels in esophageal squamous cell carcinoma (ESCC), and circ_0087378 deficiency blocked ESCC cell progression by enhancing E2F3 expression. 30 Here, we discovered that the abundance of E2F3 was raised in EC tissues and cells. Moreover, E2F3 introduction relieved the suppressive influences of miR-493-5p overexpression on EC cell development.…”
Section: Discussionmentioning
confidence: 92%
“…29 Likewise, E2F3 had elevated levels in esophageal squamous cell carcinoma (ESCC), and circ_0087378 deficiency blocked ESCC cell progression by enhancing E2F3 expression. 30 Here, we discovered that the abundance of E2F3 was raised in EC tissues and cells. Moreover, E2F3 introduction relieved the suppressive influences of miR-493-5p overexpression on EC cell development.…”
Section: Discussionmentioning
confidence: 92%
“…CircNTRK2 was increased in ESCC tissue and involved in cell metastasis. This effect of circNTRK2 may be related to its interaction with miR-140-3p to weaken its suppression on E2F3 [ 63 ]. Another report revealed that circNTRK2 also sponge miR-140-3p to regulate the expression of NRIP1, bringing about the malignant cell behaviors of ESCC, including cell migration and invasion [ 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…E2F transcription factor 3 (E2F3), a member of E2F transcription factor family that controls DNA synthesis, cell cycle, and cell death, has been underscored as a strong oncogene in numerous tumors 16–19 . Moreover, E2F3 is involved in the carcinogenic mechanism of ESCC 20–22 . Furthermore, it is still undefined whether E2F3 can work as a downstream effector of circ_0000654 in regulating ESCC development.…”
Section: Introductionmentioning
confidence: 99%